Hostility Modifies the Association between TV Viewing and Cardiometabolic Risk - Anthony Fabio; Chung-Yu Chen; Kevin H. Kim; Darin Erickson; David R. Jacobs; Janice C. Zgibor; Tammy Chung; Karen A. Matthews; Steven Sidney; Carlos Iribarren; Mark A. Pereira (Journal of Obesity)
Background. It was hypothesized that television viewing is predictive of cardiometabolic risk. Moreover, people with hostile personality type may be more susceptible to TV-induced negative emotions and harmful health habits which increase occurrence of cardiometabolic risk. Purpose. The prospective association of TV viewing on cardiometabolic risk was examined along with whether hostile personality trait was a modifier. Methods. A total of 3,269 Black and White participants in the coronary artery risk development in young adults (CARDIA) study were assessed from age 23 to age 35. A cross-lagged panel model at exam years 5, 10, 15, and 20, covering 15 years, was used to test whether hours of daily TV viewing predicted cardiometabolic risk, controlling confounding variables. Multiple group analysis of additional cross-lagged panel models stratified by high and low levels of hostility was used to evaluate whether the association was modified by the hostile personality trait. Results. The cross-lagged association of TV viewing at years 5 and 15 on clustered cardiometabolic risk score at years 10 and 20 was significant (B=0.058 and 0.051), but not at 10 to 15 years. This association was significant for those with high hostility (B=0.068 for exam years 5 to 10 and 0.057 for exam years 15 to 20) but not low hostility. Conclusion. These findings indicate that TV viewing is positively associated with cardiometabolic risk. Further, they indicate that hostility might be a modifier for the association between TV viewing and cardiometabolic risk.